2016
DOI: 10.1111/ajt.13475
|View full text |Cite
|
Sign up to set email alerts
|

The Role of TGF-β in the Association Between Primary Graft Dysfunction and Bronchiolitis Obliterans Syndrome

Abstract: Primary graft dysfunction (PGD) is a possible risk factor for bronchiolitis obliterans syndrome (BOS) following lung transplantation; however, the mechanism for any such association is poorly understood. Based on TGF-β's association with acute and chronic inflammatory disorders, we hypothesized that it may play a role in the continuum between PGD and BOS. Thus, the association between PGD and BOS was assessed in a single-center cohort of lung transplant recipients. Bronchoalveolar lavage fluid concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 45 publications
(112 reference statements)
0
31
1
1
Order By: Relevance
“…[41][42][43] We found that identification of common respiratory viruses in NP or BAL specimens was not predictive of poor outcome as measured by a composite endpoint of death, retransplant, or development of CLAD based on OB and BOS criteria. 3 In contrast to adult LTRs, ACR and PGD were not related to the development of BOS/OB or the composite endpoint.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…[41][42][43] We found that identification of common respiratory viruses in NP or BAL specimens was not predictive of poor outcome as measured by a composite endpoint of death, retransplant, or development of CLAD based on OB and BOS criteria. 3 In contrast to adult LTRs, ACR and PGD were not related to the development of BOS/OB or the composite endpoint.…”
Section: Discussionmentioning
confidence: 82%
“…3 In contrast to adult LTRs, ACR and PGD were not related to the development of BOS/OB or the composite endpoint. [41][42][43] We found that identification of common respiratory viruses in NP or BAL specimens was not predictive of poor outcome as measured by a composite endpoint of death, retransplant, or development of CLAD based on OB and BOS criteria. Although subjects with a CARV identified in NP or BAL were less likely to meet the composite endpoint, particularly when the CARV was associated with symptoms, this could be due to a competing risk bias in that subjects with good outcomes had more follow-up time to develop more viral infections.…”
Section: Discussionmentioning
confidence: 82%
“…On the one hand, it is conceivable that all injured lungs stabilize their perfusion and ventilation characteristics by 24 h but that the level of peak injury at 8 h is most predictive of their ultimate performance. This is akin to the phenomenon of ‘transient primary graft dysfunction’ whereby transient acute lung injury that resolves still has lasting effect on the allograft after transplant .…”
Section: Discussionmentioning
confidence: 99%
“…With the emergence of molecular imaging, new sensitive and selective imaging probes have been developed that can be translated from animal models to patients. Single photon emission computed tomography (SPECT) and positron emission tomography (PET) imaging can detect and monitor a variety of pathophysiological processes such as T cell activity by glucose uptake and neutrophil activation by binding of the peptide cinnamoyl-F-(D)L-F-(D)L-F (cFLFLF) to the formyl peptide receptor 1 (FPR1) (48)(49)(50). Multiphoton intravital microscopy can also be used to assess specific cell populations and functions during murine IRI (51)(52)(53).…”
Section: Introductionmentioning
confidence: 99%